Point of honor - Gethin, David (New York : Charles Scribner's Sons, 1985)
Introduces a tough, super-covert British agent named Halloran, who looks into a friend's strange death and plunges into a no-holds-barred intrigue of international importance.
Keywords: DEATH -- FICTION